Misuse of “Besides” in Spoken English: Error Patterns in Chinese University Students’ Group Discussions - Wu, Hao (JOURNAL OF LANGUAGE, 2026)
Conjunctions are essential for organizing discourse and signaling relationships between ideas, yet second language learners often struggle to use them accurately in spoken English. Among these, “besides” is particularly challenging due to its nuanced semantic and pragmatic functions. This qualitative study adopts Conversation Analysis (CA) to investigate the use of “besides” by Chinese university students in advanced English group discussions. Drawing on 15.9 hours of recorded interactional data from five Chinese undergraduates, the study identifies non-target-like uses of “besides” in naturally occurring talk. Five error types are found: misuse as a simple listing connector, misuse as an afterthought marker, overuse to connect aligned ideas, overuse as a redundant connector, and underuse as a clarifying connector. These errors stem from the complexity of “besides”, negative transfer from native-language conjunctions, instructional emphasis on surface-level coherence, and limited systematic training in spoken and written academic English. The study highlights the importance of understanding connectives in both semantic and pragmatic contexts and suggests pedagogical strategies to improve learners’ accurate and contextually appropriate use of “besides” in spoken English.